IMPLEMENTASI TOTAL QUALITY MANAGEMENT DALAM SISTEM MANAJEMEN MUTU PEMBELAJARAN DI INSTITUSI PENDIDIKAN - Achmad Supriyanto (Jurnal Cakrawala Pendidikan, 2011)
Abstract: Implementation of the Total Quality Management in the Learning Quality Management System in Educational Institutions. This study aimed to analyse the implementation of the Total Quality Management (TQM) in the learning quality management system in educational institutions. This study used a descriptive design. The population consisted of people in the organizational structure of the quality management system and the sample was pusposively selected. The data were collected through interviews and documents and were analysed using the descriptive technique. The findings show that: (1) the TQM has been implemented but it still needs optimizing, (2) it needs support from the heads of relevant units, (3) there are constraints because of work teams that are not optimal and limited time and funds, (4) the strategies to deal with the constraints depend on the condition and situation, and (5) the implementation of the TQM refers to an evaluation and monitoring study and the draft of academic quality assurance documents. Keywords: implementation, TQM, learning, education